2020
DOI: 10.1007/s00167-020-06210-2
|View full text |Cite
|
Sign up to set email alerts
|

Creation of a specialist core curriculum for the European Society for Sports traumatology, Knee surgery and Arthroscopy (ESSKA)

Abstract: Purpose The European Society for Sports traumatology, Knee surgery and Arthroscopy (ESSKA) identified the need to develop a core curriculum for clinical specialists that work within the interest areas of ESSKA. A research-based approach was used to define a set of core competencies which could be used to map all of their educational activities, resources and development priorities. This paper describes the aims, development, results and implications of this competency-based core curriculum for orthopaedic cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
3
0
2
Order By: Relevance
“…The aim of developing and implementing any curriculum including simulation training is to produce well trained and confident surgeons while safeguarding and improving patient safety [12]. It has been suggested that approximately 170 arthroscopic procedures are necessary to internalize the skills required to perform arthroscopic surgery [18].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of developing and implementing any curriculum including simulation training is to produce well trained and confident surgeons while safeguarding and improving patient safety [12]. It has been suggested that approximately 170 arthroscopic procedures are necessary to internalize the skills required to perform arthroscopic surgery [18].…”
Section: Discussionmentioning
confidence: 99%
“…ein Arzt, um ein sinnvolles, evidenzbasiertes Nachbehandlungsschema zu erstellen? Dieser Frage gingen im Jahr 2020 mehrere Arbeitsgruppen nach 18 , 30 und definierten übergreifende Fähigkeiten für Spezialist*innen in der Rehabilitation. Expert*innen zeichnen sich demnach unter anderem durch folgende Fähigkeiten aus:…”
Section: Was Ist Nötig Für Die Erstellung Evidenzbasierter Nachbehand...unclassified
“…Lind et al 18 gehen noch einen Schritt weiter, sie stellen offensichtlich infrage, dass selbst ausgewiesene Expert*innen (z. B. Operateur*innen) mit der schnellen Weiterentwicklung innerhalb der Medizin mithalten können: „Given the rapid evolution of medicine, the role of the ʼgeneralistʼ must be questioned!”…”
Section: Was Ist Nötig Für Die Erstellung Evidenzbasierter Nachbehand...unclassified
“…In the second year, it was reduced by almost half (32%), and in the following years, it continued to decrease (2006: 23.3%; 2007: 18.7%) until it fell below the acceptable 5% level in 2008. This highlights the importance of surgical experience and opens the debate about orthopedic surgeons’ adequate training time and the need for structured teaching curricula [8, 9].…”
Section: Introductionmentioning
confidence: 99%